The Knowledge of Dental Oral Health and Children’s Dental Hygiene In Sapen Elementary School, Yogyakarta - Laelia Dwi Anggraini (Interdental Jurnal Kedokteran Gigi (IJKG), 2026)
Introduction: Children often experience dental and oral health problems. Dental and oral hygiene are very important factors in maintaining dental and oral health and preventing various diseases in the oral cavity. Knowledge about dental and oral health is fundamental to maintaining dental hygiene. This study examined the relationship between the level of dental and oral health knowledge and the dental hygiene of children at Muhammadiyah Sapen Elementary School, Yogyakarta. Materials and Methods: This study utilized an observational analytical method with a cross-sectional design. Subjects were recruited using stratified sampling. Children’s dental hygiene examinations were conducted using the OHI-S index. Knowledge levels were measured using a questionnaire with the Guttman scale, and the relationship between variables was analyzed using the Spearman correlation test. Results and Discussion: The level of knowledge about dental and oral health was in the good category at 14.71%, moderate at 61.76%, and poor at 23.53%. Dental hygiene status was good at 14.71%, moderate at 64.71%, and poor at 20.58%. The Spearman correlation test obtained p = 0.01 (p < 0.05) with a correlation coefficient of 0.538, indicating a significant positive relationship between knowledge and dental hygiene. Conclusion: There is a significant relationship between the level of knowledge about dental and oral health and children’s dental hygiene at Muhammadiyah Sapen Elementary School, Yogyakarta.